2009
DOI: 10.1063/1.3103274
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of local domain patterns in [110] poled Pb(Mg1/3Nb2/3)O3–0.35PbTiO3 single crystal using a polarized Raman microprobe

Abstract: An experimental/computational procedure was presented to quantitatively analyze by polarized Raman spectroscopy (PRS) unknown domain textures in [110] poled Pb(Mg1/3Nb2/3)O3–0.35PbTiO3 single crystal. The three-dimensional domain orientation was described in terms of three Euler angles in space, and an Euler matrix was employed to transform the axial coordinates detected at the molecular scale into the laboratory coordinate frame. Raman spectral intensity of selected bands belonging to the Ag and Eg vibrationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…It has been reported that the intensity of the Raman modes for poled ferroelectrics (ceramics and single crystals) vary periodically when the samples are rotated relative to the polarization directions of the incident beam 33–38. Ge et al 37 observed the strip‐like domain patterns on the [110]‐poled PMN‐35%PT single crystal and attributed the Raman image to the domains with different orientations. In order to test whether the Raman images observed in our work originate from the special domain orientations, we tried to investigate the dependence of the Raman modes on the rotation angle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the intensity of the Raman modes for poled ferroelectrics (ceramics and single crystals) vary periodically when the samples are rotated relative to the polarization directions of the incident beam 33–38. Ge et al 37 observed the strip‐like domain patterns on the [110]‐poled PMN‐35%PT single crystal and attributed the Raman image to the domains with different orientations. In order to test whether the Raman images observed in our work originate from the special domain orientations, we tried to investigate the dependence of the Raman modes on the rotation angle.…”
Section: Resultsmentioning
confidence: 99%
“…Micro‐Raman spectroscopy has proved to be a convenient microprobe to study the local lattice structure and phase transitions in the relaxor ferroelectric materials 24–37. In recent years, the micro‐Raman mapping technique has been widely employed to investigate the domain texture in ferroelectric materials 36–38. In the presnt work, an unpoled (001)‐oriented PMN‐33%PT single crystal was investigated using the polarized Raman mapping technique.…”
Section: Introductionmentioning
confidence: 99%
“…Heterophases in relaxor ferroelectrics lead to the misfit stress of lattice and consequently allow polarization heterogeneity for accommodating the stress. , The connections between polarizataion and structure were studied on the same region of Figure b by in situ micro-Raman imaging. Raman spectroscopy has a high sensitivity to the spatial phase variation by analyzing the soft-mode. ,, Under the same ambient pressure and temperature, the phonon frequency shift is mainly attributed to the intrinsic phase difference and the internal stress inhomogeneity. , Phonon frequency mappings around 55, 80, and 585 cm –1 in Figure f–h, respectively, clearly show a larger frequency on the left side, associating with the ribbon-shaped domain configuration, while the irregular domain area corresponds to the smaller frequency values. Similarly, Hlinka et al reported a macroscopic lamellar structure in PMN-0.32PT by polarized Raman spectroscopy, indicating an array of “morphotropic” interphase boundaries between R-like and T-like areas.…”
Section: Resultsmentioning
confidence: 97%
“…It is also a local probe and hence should be very sensitive to different domain structures arising due to oxygen octahedral distortion even for short range order. Polarized Raman spectroscopy has been used successfully to obtain information about domain orientation in ferroelectric materials [15][16][17].…”
Section: Introductionmentioning
confidence: 99%